1997
DOI: 10.1073/pnas.94.12.6330
|View full text |Cite
|
Sign up to set email alerts
|

Specific complex formation between the type II bare lymphocyte syndrome-associated transactivators CIITA and RFX5

Abstract: Two of the genes defective in the five complementation groups identified in the class II-negative bare lymphocyte syndrome or corresponding laboratory mutants have been cloned. One gene encodes a protein, RFX5, that is a member of the RFX family of DNA binding proteins. The other, CIITA, encodes a large protein with a defined acidic transcriptional activation domain; this protein does not interact with DNA. Expression plasmids encoding regions of RFX5 fused to the GAL4 DNA binding domain activated transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 37 publications
3
77
0
Order By: Relevance
“…Expression of MHC class II molecules is also regulated by class II transactivator (CIITA) (Mach, 1999), which does not bind to DNA but acts as a coactivator, interacting with DNA-binding transcription factors such as regulatory factor X (RFX) family, NF-Y and CREB (Scholl et al, 1997;Zhu et al, 2000). Transcription of CIITA is regulated by CIITA promoters (CIITA-P) I -IV, each of which directs the expression of a unique first exon (MuhlethalerMottet et al, 1997): CIITA-PI is active primarily in dendritic cells and murine macrophages (Waldburger et al, 2001); CIITA-PII has been identified only in human cells, and its function remains unknown; CIITA-PIII is primarily responsible for directing constitutive expression of CIITA in B cells, and can drive CIITA expression after IFN-g stimulation in endothelial cells, fibroblasts or melanocytes (Piskurich et al, 1998;Deffrennes et al, 2001), and CIITA-PIV is a major regulator of IFN-g-inducible expression of CIITA (Muhlethaler-Mottet et al, 1997).…”
mentioning
confidence: 99%
“…Expression of MHC class II molecules is also regulated by class II transactivator (CIITA) (Mach, 1999), which does not bind to DNA but acts as a coactivator, interacting with DNA-binding transcription factors such as regulatory factor X (RFX) family, NF-Y and CREB (Scholl et al, 1997;Zhu et al, 2000). Transcription of CIITA is regulated by CIITA promoters (CIITA-P) I -IV, each of which directs the expression of a unique first exon (MuhlethalerMottet et al, 1997): CIITA-PI is active primarily in dendritic cells and murine macrophages (Waldburger et al, 2001); CIITA-PII has been identified only in human cells, and its function remains unknown; CIITA-PIII is primarily responsible for directing constitutive expression of CIITA in B cells, and can drive CIITA expression after IFN-g stimulation in endothelial cells, fibroblasts or melanocytes (Piskurich et al, 1998;Deffrennes et al, 2001), and CIITA-PIV is a major regulator of IFN-g-inducible expression of CIITA (Muhlethaler-Mottet et al, 1997).…”
mentioning
confidence: 99%
“…Reconstitution of the RB-de®cient H2009 human SCLC line with wild type RB restores IFN-g-responsiveness at the DRb locus, but not at the DRa locus, indicating the existence of a speci®c factor required for induction of DRa (Lu et al, 1996). Indeed, several transcription factors have been shown to speci®cally modulate one or a subset of cII genes (Borras et al, 1995;Scholl et al, 1996). However, other than the current study on RB, no genetic experiments have been carried out to determine if these factors are essential for normal cII-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptional co-factor, known as the class II trans-activator (CIITA), is also required for transcription of MHC class II genes (Steimle et al, 1993). CIITA does not bind DNA, but rather is recruited to MHC class II promoters by interacting with the CREB protein and subunits of the RFX and NFY complexes (DeSandro et al, 2000;Hake et al, 2000;Scholl et al, 1997;Zhu et al, 2000). In addition, the role of the W box in recruiting CIITA to MHC class II promoters is critical, though the factor(s) that binds this element have not been identified (Brown et al, 1998;Muhlethaler-Mottet et al, 2004).…”
Section: Introductionmentioning
confidence: 99%